Deinstitutionalization in Mental Health in Primary Health Care: a literary review (Revista Brasileira Multidisciplinar, 2026)
Purpose: this study aims to identify, through an integrative literature review, the relationship of Primary Health Care in the deinstitutionalization mental health process. Methodology: An integrative literature review was carried out, and articles were searched in databases using keywords and synonyms: "Primary Health Care / Primary Care", "Mental Health", "Mental Health Care" and “Deinstitutionalization”. 108 articles were found, of which five were included to compose the final sample. Results: The language of the entire sample is Portuguese and the articles were published in a period ranging from 2012 to 2019. All articles deal with qualitative methodology and predominance of the exploratory type, through semi-structured interviews. All studies work with a common target public, Primary Health Care professionals. Conclusion: Primary Health Care has a unique role in the deinstitutionalization in mental health, process by providing users with the right to treatment in their territory, with completeness and equity. There are still gaps to be filled when it comes to Primary Health Care professionals empowerment, given that this topic needs attention and needs to be further explored.
Keywords: Mental health; Primary Health Care; Mental Health Assistance; Deinstitutionalization